UNRAVELLING THE VISION OF PEACE AND UNITY A CRITICAL DISCOURSE ANALYSIS OF JOHN LENNON'S IMAGINE - Alan Jaelani; Nuraeni Nuraeni; Eska Perdana Prasetya; Sarvar Juraboev; Annisa Ayu Fadhilah; Indah Dwi Rizky; Monalisa Monalisa (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2023)
This research investigates the iconic and timeless masterpiece song